New Approach for Estimation of Zonal Efficiency of Air Exchange Organization - Dovhaliuk, Volodymyr; Mileikovskyi, Viktor; ., . (International Journal of Engineering and Technology, 2018)
Energy efficiency of buildings is dependent on air exchange organization. There are different methods for efficiency estimation of it. As it is shown in literature review, they have significant limitations including non-obvious physical meaning, which cause problems in validation of the results. Certain of them are not acceptable for zonal ventilation in rooms. Previous author’s work introduces new approach for the efficiency estimation of air exchange in a single-zone or multi-zonal rooms, which has obvious physical meaning – relation of demands and supplied potentials. It provides the efficiency value for whole room only. In this work, by the similar approach, a method is proposed for estimation of zonal air exchange efficiency in different kind of rooms for each occupied zone separately. Additional definitions are introduced for the parameters and demands estimation in each occupied zone. The example of efficiency estimation of air exchange in a museum room with constant air volume system of air conditioning is solved. Sheltering of the keeping zone is recommended for the maximum air exchange efficiency.